AKTIVITAS METAKOGNISI DALAM PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI GENDER SISWA KELAS VII SMP NEGERI 1 NANGGULAN KABUPATEN KULON PROGO - Sari, Retno; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2016)
Abstract: This research was aimed to decribe metacognition activity of male and female students in mathematics problem solving. This research was a qualitative research which used case study method. The subject of the research was 7th students of SMP Negeri 1 Nanggulan. The subject selection criteria was based on students opinion expressing competency either in spoken and written form. The data was collected using think aloud method where the students were asked to express their ideas and questions loudly in mathematical problem solving processes. Then the time triangulation was run to produce a valid data from the research subject. The data analysis was conducted using Miles and Huberman model. The result of research showed : 1) the metacognition activity of the male students are : a) understanding the problems phase : perform activities related to strategic knowledge; b) devising a plan phase : perform activities associated with knowledge about cognitive tasks; c) carrying out the plan phase : perform activities related to strategic knowledge and associated with knowledge about cognitive tasks; d) looking back phase : perform activities related to knowledge strategy and perform activities associated with self-knowledge. 2) the metacognition activity of the female students are : a) understanding the problems phase: perform activities related to strategic knowledge and perform activity associated with self-knowledge; b) devising a plan phase : perform activity associated with knowledge about cognitive tasks; c) carrying out the plan phase : perform activity related to strategic knowledge and associated with knowledge about cognitive tasks; d) looking back phase: perform activities related to strategic knowledge and Â perform activity associated with self-knowledgeKeywords: metacognition, mathematics problem solving, genderÂ